Answer
a = 3.674 m / s ^ 2
t = 3.13 s
Using the kinematic equations for the movement we have:
(1)
(2)
Where:
= initial position
= initial velocity
a = acceleration
t = time in seconds
= final speed
We know:
![P_(0)=0](https://img.qammunity.org/2019/formulas/physics/middle-school/bzgnmw5yop4ns59gep3z6zl870z21g9r05.png)
![V_(0)= 0](https://img.qammunity.org/2019/formulas/physics/middle-school/wj6gf6nawoi3inqgbybuospdlz3osq6yts.png)
h = 18 m
![V_(f) = 11.5(m)/(s)](https://img.qammunity.org/2019/formulas/physics/middle-school/pne2m9jiologl5d60kiesz2ttxolhy6c6l.png)
So:
From (2) we have that:
![t =(V_(f))/(a)](https://img.qammunity.org/2019/formulas/physics/middle-school/vs2071yp7713ipae5y6gkg2702hwx6pbkf.png)
![t =(11.5)/(a)](https://img.qammunity.org/2019/formulas/physics/middle-school/cvjkuwsjswzw3o94mvvdhx88wq89zusu98.png)
From (1) we have to:
![h (t) = 0.5at ^ 2\\h = 18 = 0.5at ^ 2](https://img.qammunity.org/2019/formulas/physics/middle-school/u9s3jiae54nled618lr1eh9j2r15qpi6wk.png)
Then we clear "a" to find the acceleration.
![(36)/(t^2) = a\\a = (36)/(((11.5)/(a))^2) \\\\a =(11.5^2)/(36)\\a = 3.674 m / s ^2](https://img.qammunity.org/2019/formulas/physics/middle-school/1lqgii7oicw4wcaqcuznkogx83bj4avrtc.png)
Then, the time it takes to reach this speed is:
![t =(V_(f))/(a)\\t =(11.5)/(3.674)\\t = 3.13 s](https://img.qammunity.org/2019/formulas/physics/middle-school/wz5hi6i4sh51e2m9hqlpl2dj0n3wli8lw5.png)